Effect of SiC Particulate on Short Glass Fiber Reinforced Polyester Composite in Erosive Wear Environment - Ritesh KAUNDAL; Amar PATNAIK; Alok SATAPATHY (Walailak Journal of Science and Technology, 2012)
This study reports the effect on impact strength, physical properties and erosion behavior of silicon carbide (SiC) (0 wt%, 10 wt%, 20 wt%) filled short glass fibers (GF) on reinforced polymer composites. The effect of various operational variables, material parameters and their interactive influences on erosive wear behavior of these composites has been studied systematically. It is observed that silicon carbide (SiC) reinforced glass fiber reinforced polymer composites exhibit better erosion resistance as compared with unfilled polymer composite. However, in particulate filled composites the maximum erosion rate takes place at an impingement angle of 75 ° and for unfilled composite the maximum erosion takes place at an impingement angle of 60 °. In this investigation, the physical and mechanical properties of all the unfilled and particulate filled composites are also evaluated for structural applications.